Reduced burden of antibiotic prescription in an italian pediatric primary care clinic during the first wave of COVID-19 pandemic: a shot in the arm for antimicrobial resistance? - Alice Monzani; Giulia Minelli; Ivana Rabbone (BMC, 2023)
Abstract Rates of antibiotic-resistant bacteria have increased worldwide over recent years, but the Italian Institute of Health reported a disruption to this trend in 2021 compared with 2020. Children are often recipients of unnecessary antibiotic prescriptions, especially for respiratory tract infections (RTIs). During the initial phase of the COVID-19 pandemic, common RTIs substantially decreased, so it is conceivable that antibiotic prescriptions also reduced during this time. To test this hypothesis, we retrospectively collected data on all visits to a pediatric primary care clinic in Northern Italy from February 20, 2020 to June 2, 2020 and compared data with the same period in 2019. We evaluated the antibiotic prescription rate according to the diagnosis at discharge. While the total number of visits significantly decreased (1335 in 2020 vs. 4899 in 2019), there was only a slight reduction in the antibiotic prescription rate (1039 in 2019, 21.2%, vs. 272 in 2020, 20.4%). However, this corresponded to a 73.8% decrease in the total number of antibiotic prescriptions, with antibiotics for RTI accounting for 69% of the total reduction. It is possible that, at the larger scale, reduced antibiotic prescription in pediatrics during the COVID-19 pandemic resulted in a slight reduction in antimicrobial resistance.